2022
DOI: 10.1021/acsinfecdis.2c00326
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Pyrido[1,2-a]benzimidazoles Exert Strong Parasiticidal Effects by Achieving High Cellular Uptake and Suppressing Heme Detoxification

Abstract: Pyrido­[1,2-a]­benzimidazoles (PBIs) are synthetic antiplasmodium agents with potent activity and are structurally differentiated from benchmark antimalarials. To study the cellular uptake of PBIs and understand the underlying phenotype of their antiplasmodium activity, their antiparasitic activities were examined in chloroquine (CQ)-susceptible and CQ-resistant Plasmodium falciparum in vitro. Moreover, drug uptake and heme detoxification suppression were examined in Plasmodium berghei-infected mice. The in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Compounds (103-105) reported strong binding interactions with wild and mutant type PfDHFR-TS in docking analysis and in vitro study shown as the most potent antimalarial property with low toxicity and high selectivity. [118] Next, they also synthesized tetrahydrobenzo [4,5]thieno[2,3- In their experiments, Murwih et al used the Claisen-Schmidt condensation to synthesised the thiophene derivatives (108)(109)(110). Through a ring-closing process involving the previously synthesized chalcones, twelve pyrazolines and eight pyrimidines have been synthesized.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds (103-105) reported strong binding interactions with wild and mutant type PfDHFR-TS in docking analysis and in vitro study shown as the most potent antimalarial property with low toxicity and high selectivity. [118] Next, they also synthesized tetrahydrobenzo [4,5]thieno[2,3- In their experiments, Murwih et al used the Claisen-Schmidt condensation to synthesised the thiophene derivatives (108)(109)(110). Through a ring-closing process involving the previously synthesized chalcones, twelve pyrazolines and eight pyrimidines have been synthesized.…”
Section: Othersmentioning
confidence: 99%
“…Sousa and co-workers reported pyrido[1,2-a]benzimidazole (95) acting on the trophozoites of P. falciparum with IC 50 of 60.8 nM (Pf3D7) and 58.8 nM (PfW2) along with its exhaustive in vitro and in vivo profile claiming it as the suitable drug candidate for malaria. [109] Patel and co-workers reported the imidazole derivative (96) against P. falciparum with IC 50 of 0.15 μg/mL with reference to quinine (IC 50 of 0.268 μg/mL). [110] Further, it has been also investigated for its potential against S. aureus, E. coli and M. tuberculosis along with the additional in silico molecular docking and ADMET studies.…”
Section: Othersmentioning
confidence: 99%
“…Sousa et al . [ 85 ] identified three potent pyrido [ 1 ,2- a ]benzimidazole inhibitors 6a-c endowed with comparable in vitro activities against 3D7 and CQ-resistant W2 strains (Table 6 ). In particular, 6a was found to be the most effective, and so it was selected for addressing further studies on the mechanism of action, using some conventional drugs for the purpose of comparison.…”
Section: Benzimidazole-based Compounds Active Against Malaria Leishma...mentioning
confidence: 99%